Strategi UMKM Mempertahankan Pelanggan di Era Digitalisasi - Iswara S, I Made Ardhy Kusuma; Mahyuni, Luh Putu (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
MSME activities in the digitalization era are required to be able to apply digital technology. To maintain customer loyalty, MSMEs must maintain a company image, improve service quality and pay attention to the price of a product. This study aims to determine and analyze the strategies of MSMEs to retain customers in the digitalization era. This research is qualitative research. The location of this research is in Bualu Traditional Village, Badung Regency, South Kuta District, Benoa Village. Informants were determined by purposive sampling, namely the community and MSME players (micro, small and medium enterprises) located in the Bualu Traditional Village. Data collection techniques were carried out by interview, observation and documentation. Data validity is done by triangulation and data analysis is done by collecting data, reducing data, presenting data and drawing conclusions. The results of this study indicate that in maintaining customers, MSME actors have provided good quality service, are friendly and polite, and pay attention to customer needs. In addition, other factors, namely image and price, also influence maintaining customers so that the existence of MSMEs in Bualu Traditional Village still survives and is able to develop in the current era of digitalization